Corporate Governance and Financial Performance: Empirical Evidence from LQ-45 Firms in Indonesia - Nanda ’Ainurrohmah; Agrianti Komalasari; Reni Oktavia (ROE: Research of Economics and Business, 2026)
This study examines the effect of corporate governance on the financial performance of firms listed in the LQ-45 index of the Indonesia Stock Exchange during the 2020–2024 period. This study is among the first to investigate governance effectiveness in the post-COVID-19 period by focusing on blue-chip firms in an emerging market context. Using panel data analysis and a Random Effects Model, corporate governance is measured through a composite governance disclosure index, while financial performance is proxied by Return on Assets (ROA). The empirical results indicate that corporate governance has a positive and statistically significant effect on firm performance. These findings support agency theory, suggesting that stronger governance mechanisms improve managerial efficiency and mitigate agency conflicts, particularly under post-pandemic economic uncertainty. By providing updated evidence from highly liquid Indonesian firms, this study contributes to the corporate governance literature and offers practical implications for regulators, corporate managers, and investors seeking to enhance firm performance through improved governance practices.